Assessment of the Cerebral Hemodynamic Benefits of Carotid Artery Stenting for Patients with Preoperative Hemodynamic Impairment Using Cerebral Single Photon Emission Computed Tomography (SPECT) and Carbon Dioxide Inhalation - Chen, Da-Wei (Med Sci Monit, 2018)
BACKGROUND: The aim of this study was to evaluate the effects of carotid artery angioplasty and carotid artery stenting (CAS) on cerebral blood flow (CBF) and cerebrovascular reactivity (CVR) in patients with preoperative cerebrovascular hemodynamic impairment. MATERIAL/METHODS: Seventeen patients with unilateral severe internal carotid artery (ICA) stenosis and ipsilateral CVR impairment underwent CAS. CBF and CVR were measured by single photon emission computed tomography (SPECT) with inhalation of carbon dioxide (CO(2)) one week before and three months after CAS. Sixty-eight ROIs in the middle cerebral artery (MCA) territory were analyzed in 17 patients. RESULTS: Before CAS, CVR was impaired in all ROIs. CBF was impaired in 16 ROIs (23.5%). The percentage of ROIs with impaired CBF was significantly increased in patients with ≥90% carotid artery stenosis (p=0.047) without collateral flow through the circle of Willis (p=0.005). CAS significantly increased CVR in ROIs with a normal preoperative CBF and impaired CVR, indicating mild hemodynamic impairment (0.9±6.7% vs. 4.9±8.6%) (p=0.014). CAS significantly increased CBF in ROIs with preoperative impaired CBF and impaired CVR, indicating severe hemodynamic impairment (79.1±7.5% vs. 86.7±10.0%) (p<0.001). Following CAS, ROIs with normal CBF and impaired CVR had a significantly increased percentage of improved CVR (p=0.047); ROIs with impaired CBF and impaired CVR had a significantly increased percentage of improved CBF (p=0.027). CONCLUSIONS: The severity of preoperative hemodynamic impairment, which is related to the degree of carotid artery stenosis and cerebral collateral flow, may influence hemodynamic benefits by CAS.